Towards sustainable management of mixed dipterocarp forests of South-east Asia: moving beyond minimum diameter cutting limits - Sist, P.; Fimbel, R.; Sheil, Douglas; Nasi, Robert; Chevallier, M.H. (2003)
Selective logging applied in tropical forests is based on one universal criterion: a minimum diameter cutting limit for all commercial timber species. Minimum diameter cutting limits in mixed dipterocarp forests of the Malesia region lead to high felling intensities (10–20+ trees per hectare). Such extraction rates create massive stand damage (>50% of the remaining tree population), which has a negative impact on the regeneration and growth of many harvested dipterocarp species. As such, the minimum diameter cutting limit approach is seldom compatible with sustainable forest management. Where basic ecological characteristics of the commercial species are considered in timber harvesting prescriptions, mixed dipterocarp forests appear capable of sustained timber yields, habitat conservation, and providing other goods and services. This paper first presents the main silvicultural systems developed in mixed dipterocarp forests of Western Malesia and then reviews current knowledge of dipterocarp biology to finally develop guidelines aimed at improving the ecological sustainability of production forests of Western Malesia. These guidelines, a pragmatic reflection of science and ‘best guess’ judgement, include: (1) integration of reduced-impact logging practices into normal management operations; (2) cutting of eight trees per hectare or less (with a felling cycle of 40–60 years to be determined according to local conditions); (3) defining minimum diameter cutting limits according to the structure, density and diameter at reproduction of target species; (4) avoiding harvesting species with less than one adult tree per hectare (diameter at breast height [dbh] larger and equal to 50cm over an area of 50–100 ha); (5) minimizing the size and connectivity of gaps (<600m2 whenever possible); (6) refraining from treatments such as understorey clearing; and (7) providing explicit protection for key forest species and the ecological processes they perform. Further refinement is encouraged to allow for local conditions, and for other forest types.